PENGARUH KOMPONEN CITRA MEREK (BRAND IMAGE) TERHADAP LOYALITAS KONSUMEN PRODUK MINUMAN SHARE TEA DI KOTA MANADO - Gabriella Susana Tineke Ransulangi; Nordy F. L. Waney; Joachim N. K. Dumais (Sam Ratulangi University, 2017)
This study aims to determine the influence of brand image on consumer loyalty Share Tea drink in the city of Manado. In its development, bubble tea drinks into today's drinks with a variety of flavor variants that can attract consumers in all ages. Reach back the market that has declined, and to maintain the market it has gained is a challenge that Share Tea companies must face in creating consumer loyalty. This study uses data obtained from questionnaires, observations and direct interviews with the manager of Tea Share in Manado City. The analysis technique used is multiple regressions. From this research can be concluded that Components of brand image consisting of coorporate image, user image, and product image has a influence on Consumer Loyalty. The components of the brand image together have a positive influence on consumer loyalty. The coorporate image and user image individually does not significantly affect consumer loyalty, while product image individually has a significant effect on consumer loyalty.